Réponses

2013-10-13T19:10:49+02:00
A = 3/11 - 8/9 + 2/3= 27/99-88/99+66/99=5/99

B = (2/3 - 3/5) x (1/6 - 3/4)= (10/15-9/15)*(2/12-9/12)=6/15*(-7/12)= 2/5*(-7/12)= -7/10

C = 5/9 + 3/9 x -2/5= 5/9+ (-6/45)= 5/9-2/15= 75/135-18/135=57/135=19/45

D = 3/7 - (1/6 - 5/2) + -2/3
Meilleure réponse !
2013-10-13T19:12:28+02:00
A = 3/11 - 8/9 + 2/3
= -61/99 + 2/3
= 5/99

B = ( 2/3 - 3/5 ) x ( 1/6 - 3/4 )
= 1/15 x (-7/12)
= -7/180

C = 5/9 + 3/9 x -2/5
= 5/9 - 2/15
= 19/45

D = 3/7 - ( 1/6 - 5/2 ) + -2/3
= 3/7 + 7/3 - 2/3
= 58/21 - 2/3
= 44/21